Liquid chromatography-inductively coupled plasma mass spectrometry analysis of peptides labelled with ClickZip mass tags - Myšková, Aneta; David, Tomáš; Šedinová, Miroslava; Demirci, Ibrahim; Polasek, Miloslav; Kuneš, Jaroslav; Maletínská, Lenka; Sýkora, David; Kaňa, Antonín (Analytica chimica acta, 2025)
Lipidated anorexigenic peptides are highly promising compounds for the treatment of obesity and related diseases. However, their exact mechanism of action still remains unknown. We labelled a lipidated analogue of an anorexigenic prolactin-releasing peptide (palm11-PrRP31) with an extremely stable ClickZip lanthanide tag, facilitating tracking of the peptide within the organism. We then employed a separation method based on liquid chromatography combined with inductively coupled plasma mass spectrometry (LC-ICP-MS). This technique involved the use of an unconventional mobile phase containing 5 % 1,2-hexanediol in H2O (v/v) with the addition of 2 % formic acid. Using a rapid. 6-min analysis, we were able to quantify the ClickZip tag - and thus indirectly the fate of the labelled peptides in the living organism - independently of free Ln3+ ions. The detection limits for the various lanthanide chemical forms were extremely low, ranging between 0.9 and 3.4 ng/L. We demonstrated the suitability of the method for analysing real biological samples like blood plasma, and confirmed the accuracy of our results. Prior to LC-ICP-MS analysis, we optimised a process involving the microwave-assisted digestion of liver samples to preserve the integrity of the ClickZip tag. We also identified several metabolites of the labelled peptides in the liver, urine, and blood plasma, highlighting the utility of the method for revealing the mechanism of action behind the labelled lipopeptides.
Keywords: lanthanoidy; myši; Peptides; peptidy; Animals; Click Chemistry; zvířata; Mass Spectrometry; Mice; Chromatography, Liquid; Sample digestion; Method validation; 1,2-Hexanediol; Lanthanoid Series Elements; hmotnostní spektrometrie; chromatografie kapalinová; Anorexigenic peptides; click chemie